2022
DOI: 10.1093/infdis/jiac229
|View full text |Cite
|
Sign up to set email alerts
|

People With Human Immunodeficiency Virus Receiving Suppressive Antiretroviral Therapy Show Typical Antibody Durability After Dual Coronavirus Disease 2019 Vaccination and Strong Third Dose Responses

Abstract: Background Longer-term humoral responses to two-dose COVID-19 vaccines remain incompletely characterized in people living with HIV (PLWH), as do initial responses to a third dose. Methods We measured antibodies against the SARS-CoV-2 spike protein receptor-binding domain, ACE2 displacement and viral neutralization against wild-type and Omicron strains up to six months following two-dose vaccination, and one month following th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 49 publications
14
41
1
Order By: Relevance
“…In line with our previous observations on the HIV-infected subjects receiving the primary vaccination [13], we observed that neither age, sex, BMI, nadir CD4+, baseline CD4+ nor cART regimen significantly affected the humoral response after the third dose. These findings are consistent with what was reported by Jedicke et al with respect to nadir and current CD4+ [14] and by Lapointe et al with respect to nadir CD4+ [12]. Differently from what emerged from our study, the ORCHESTRA project, which investigated the humoral immune response to the booster dose with our same vaccine in PLWH, demonstrated that a CD4+ count <200 cell/mm 3 at baseline was significantly associated with a lower antibody response in comparison with a CD4+ count >500 cell/mm 3 [15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our previous observations on the HIV-infected subjects receiving the primary vaccination [13], we observed that neither age, sex, BMI, nadir CD4+, baseline CD4+ nor cART regimen significantly affected the humoral response after the third dose. These findings are consistent with what was reported by Jedicke et al with respect to nadir and current CD4+ [14] and by Lapointe et al with respect to nadir CD4+ [12]. Differently from what emerged from our study, the ORCHESTRA project, which investigated the humoral immune response to the booster dose with our same vaccine in PLWH, demonstrated that a CD4+ count <200 cell/mm 3 at baseline was significantly associated with a lower antibody response in comparison with a CD4+ count >500 cell/mm 3 [15].…”
Section: Discussionsupporting
confidence: 93%
“…Consistently with the pilot study conducted with the BNT162b2 vaccine in the general population [9], we observed that the booster dose significantly increased the humoral response of HIV-infected subjects with respect to the primary vaccination. Our findings are in line with those by others in PLWH who received an RNA-based booster vaccination, although mostly with the mRNA-1273 vaccine [12]. The evidence of a greater humoral immunity elicited by the booster dose compared with primary vaccination alone was also confirmed by another study in PLWH that, however, used an inactivated COVID-19 booster vaccination [11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among PLWH, our results show no ideal but favorable seroconversion rate even after a second dose of COVID-19 vaccine, prompting the requirement for additional measures (such as a booster vaccination). Lapointe et al showed that in PLWH, the humoral response after the third dose greatly exceeded the level after the second dose, especially for the mRNA-1273 vaccine (Moderna, Cambridge, MA, USA) ( Lapointe et al, 2022 ). In an observational study, Barda et al showed that a third dose of the BNT162b2 vaccine was effective in protecting individuals against severe COVID-19-related outcomes, compared with receiving only two doses at least five months ago ( Barda et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that PLWH are at higher risk of severe coronavirus disease 2019, 2 immunological data following vaccination in this population remain sparse. [3][4][5][6] We prospectively evaluated humoral and T-cell immune responses before (T0) and after (T1) administration of a third dose of SARS-CoV-2 vaccine, either BNT162b2 or mRNA-1273, in PLWH followed-up at the University Hospital of Liège (Belgium) and in HIV-negative healthcare workers (HCWs). Biological analyses included quantification of anti-trimeric spike protein specific IgG (anti-S IgG), 50% neutralising antibody titres (NT 50 ) against wildtype (WT) and Omicron (BA.1/B.1.1.529) strains, and SARS-CoV-2specific interferon-gamma (IFN-γ ) release using the QuantiFERON SARS-CoV-2 assay which contains two different pools (Ag1 and Ag2) of spike-embedded peptides (Appendix p1-2).…”
mentioning
confidence: 99%